THE EFFECTIVENESS OF USING TED TALKS VIDEO IN IMPROVING STUDENTS PUBLIC SPEAKINGS SKILLS IN SENIOR HIGH SCHOOL - Miftah Farid (JALL (Journal of Applied Linguistics and Literacy), 2019)
This study tried to analyse the effectiveness of using TED talks video in improving students public speaking skill and also the students’ perception about using TED talks video in improving students’ public speaking skills. Participant of this study were thirty four students. A mixed method was used to collect quantitative and qualitative data. To achieve the aims of this study,      pre-test and post-test were administered as the quantitative data collection, and close-ended questionnaires as the qualitative data collection. From the data taken, the result showed that the students’ perception about using TED talks video in improving students’ public speaking skills is that the students response positively towards how the writer taught them. In addition, the data showed that the writer used a variety of instructional methods to reach the teaching objectively and the strategies were tried to find based on the students need in many ways. Therefore, it was concluded that the use of TED Talks is very useful to improve students’ public speaking skill.  Key words: Effectiveness, Ted Talks Video, Public Speaking Skills